2006
DOI: 10.1039/b517030c
|View full text |Cite
|
Sign up to set email alerts
|

The electronic structure of nitrilimine: absence of the carbenic form

Abstract: The electronic structure of nitrilimine HCNNH is shown to essentially be propargylic by CASSCF and Spin-Coupled (modern VB) calculations; in contrast to a recent claim, the carbenic resonance form is absent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 18 publications
1
14
0
Order By: Relevance
“…However, Ponti and co-workers have used CASSCF and spin-coupled calculations to show that the most important electronic structure of nitrilimines corresponds to the propargylic resonance form with little or no carbenic character. [71] …”
Section: Configuration Mixing Modelsmentioning
confidence: 97%
“…However, Ponti and co-workers have used CASSCF and spin-coupled calculations to show that the most important electronic structure of nitrilimines corresponds to the propargylic resonance form with little or no carbenic character. [71] …”
Section: Configuration Mixing Modelsmentioning
confidence: 97%
“…[20] Different ways to describe the geometric and electronic structures of the parent nitrile imine have also been reported by means of valence bond (VB) calculations. [13,21] Scheme 1. Different resonance forms that can represent the structure of a nitrile imine.…”
Section: Introductionmentioning
confidence: 99%
“…More recent DFT calculations in combination with the natural resonance theory indicated that all four resonance structures are necessary for a full description and that the carbenic form dominates for F-CNN-F and H 2 N-CNN-NH 2 8. In contrast, a spin-coupled valence bond calculation using the geometry from a CASSCF calculation suggested that the stable electronic structure of H-CNN-H is predominantly propargylic 9. To provide direct evidence, herein we report the use of photocrystallography10 to observe for the first time the structure of a non-stabilized nitrile imine generated photochemically in situ in the solid state.…”
mentioning
confidence: 99%